Customer Effort in Value Cocreation Activities: Improving Quality of Life and Behavioral Intentions of Health Care Customers. (August 2015) - Sweeney, Jillian C.; Danaher, Tracey S.; McColl-Kennedy, Janet R.
Transformative service research is particularly relevant in health care where the firm and customer can contribute to individual as well as societal well-being. This article explores customer value cocreation in health care, identifying a hierarchy of activities representing varying levels of customer effort from complying with basic requirements (less effort and easier tasks) to extensive decision making (more effort and more difficult tasks). We define customer Effort in Value Cocreation Activities (EVCA) as the degree of effort that customers exert to integrate resources, through a range of activities of varying levels of perceived difficulty. Our findings underscore the importance of viewing health care service as taking place within the customer's service network that extends well beyond the customer-firm dyad to include other market-facing as well as public and private resources. Moreover, we demonstrate the transformative potential of customer EVCA linking customer EVCA to quality of life, satisfaction with service and behavioral intentions. We do so across three prevalent chronic diseases—cancer, heart disease, and diabetes. Our findings highlight how an integrated care model has benefits for both customers and providers and can enhance customer EVCA.